Expanding the mutation and phenotype spectrum of MYH3-associated skeletal disorders - Zhao, Sen; Zhang, Yuanqiang; Hallgrimsdottir, Sigrun; Zuo, Yuzhi; Li, Xiaoxin; Batkovskyte, Dominyka; Liu, Sen; Lindelöf, Hillevi; Wang, Shengru; Hammarsjö, Anna; Yang, Yang; Ye, Yongyu; et al. (Npj genomic medicine, 2022)
Pathogenic variants in MYH3 cause distal arthrogryposis type 2A and type 2B3 as well as contractures, pterygia and spondylocarpotarsal fusion syndromes types 1A and 1B. These disorders are ultra-rare and their natural course and phenotypic variability are not well described. In this study, we summarize the clinical features and genetic findings of 17 patients from 10 unrelated families with vertebral malformations caused by dominant or recessive pathogenic variants in MYH3 . Twelve novel pathogenic variants in MYH3 (NM_002470.4) were identified: three of them were de novo or inherited in autosomal dominant way and nine were inherited in autosomal recessive way. The patients had vertebral segmentation anomalies accompanied with variable joint contractures, short stature and dysmorphic facial features. There was a significant phenotypic overlap between dominant and recessive MYH3 -associated conditions regarding the degree of short stature as well as the number of vertebral fusions. All monoallelic variants caused significantly decreased SMAD3 phosphorylation, which is consistent with the previously proposed pathogenic mechanism of impaired canonical TGF-β signaling. Most of the biallelic variants were predicted to be protein-truncating, while one missense variant c.4244T>G,p.(Leu1415Arg), which was inherited in an autosomal recessive way, was found to alter the phosphorylation level of p38, suggesting an inhibition of the non-canonical pathway of TGF-β signaling. In conclusion, the identification of 12 novel pathogenic variants and overlapping phenotypes in 17 affected individuals from 10 unrelated families expands the mutation and phenotype spectrum of MYH3 -associated skeletal disorders. We show that disturbances of canonical or non-canonical TGF-β signaling pathways are involved in pathogenesis of MYH3 -associated skeletal fusion (MASF) syndrome.